Mommas Boys and Natures Girls: Explaining Differences in Risk Attitudes between Women and Men (Global Journal of Human-Social Science, 2012)
Extensive research shows that men report greater enjoyment and excitement from taking risks than do women What remains to be answered is why women seem to exhibit risk attitudes that are less aggressive than men In this paper we apply aspects of power-control theory PCT as a theoretical foundation for explaining generalized risk-taking attitudes among women and men We investigate the role of socialization from mothers in shaping the risk attitudes of their children Using data from the NLSY mothers were found to have little influence on the risk attitudes on daughters although mothers SES may impart a profound influence on sons risk tolerances It was also noted that children s personality trait profiles were positively associated with their risk attitudes although the effects for boys differed from those of girls
Keywords: risk attitudes; gender; power control theory; socialization